MENEMUKENALI KONSEP ETIKA DAN SIKAP KONSELOR PROFESIONAL DALAM BIMBINGAN DAN KONSELING - Desi Alawiyah; Hayatul Khairul Rahmat; Syahti Pernanda (Institut Agama Islam Muhammadiyah Sinjai, 2020)
The complexity of the problems faced by students today, of course, is followed by the endurance of the individual both physically and psychologically. Therefore, a counselor should have sufficient insight, knowledge, skills, values, and attitudes in carrying out guidance and counseling services for all types of diversity in order to create a professional counselor. Therefore, this paper tries to identify the ethical concepts and attitudes of professional counselors in guidance and counseling so that later professional counselors are formed in terms of ethics, attitudes, and personal qualities of the counselors. This writing uses a literature study approach and content analysis techniques. The findings in this paper are (1) the counselor's professional ethics are the rules of behavior that become a reference for the counselor in carrying out his duties or responsibilities in providing guidance and counseling services to the counselee; (2) the counselor's professional attitude includes being responsible, caring about professional identity and professional development, having an awareness of commitment, being skilled at using special techniques developed on the basis of broad insights and scientific principles, understanding and managing personal and professional strengths and limitations. and maintaining objectivity and maintaining the counselee's problems, and (3) the efforts made by the counselor in developing his professional attitude and ethics, namely by developing attitudes during pre-service education and developing attitudes during his tenur